The Influence of LKP Managerial Ability on Job Opportunities for Training Participants through Job Skills Education Program - Puspitasari, Savira Widya; Febriansa, Febriansa; Qodriyati, Tri Ulya (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2025)
LKP’s managerial ability is one of the keys to being able to run an institution in achieving its goals in improving the quality of training participants, so that training participants are able to complete for job opportunities with DUDI partners. LKP's good managerial ability, which is also supported by the results of quality training participants, increases the job opportunities of trainees at DUDI partners. The research objectives (1) to determine the managerial ability of LKP in Malang City, (2) to determine the job opportunities of training participants in business partners and the industrial world through the Job Skills Education Program (PKK), (3) to determine the effect of LKP managerial abilities on opportunities the work of training participants for business partners and the industrial world through the Employment Skills Education Program (PKK). LKP managerial ability has a significant effect on the job opportunities of trainees at DUDI partners. Thus, simultaneously, the LKP managerial ability variable has a positive and significant effect on the job opportunities of the trainees.